Venous thromboembolism in patients with liver diseases. (3rd October 2018) - Barba, R.; Gonzalvez‐Gasch, Asuncion; Joya Seijo, D.; Marco, J.; Canora, J.; Plaza, S.; Angelina García, M.; Zapatero, A.
Abstract : Essentials Emerging evidence shows that patients with liver disease are not protected from thrombotic events. We assessed the risk of venous thromboembolism (VTE) in patients with liver disease. The presence of VTE resulted in an increase in mortality for patients with liver disease. Hospitalized patients with moderate‐severe liver disease had low risk of VTE during admission. Summary: Background and Aims: Patients with liver disease were traditionally believed to be protected against development of blood clots, but some studies have shown a potential increased risk of venous thrombotic complications. We assessed the risk of venous thromboembolism (VTE) in patients with liver disease. Methods: Data in discharge reports of patients with liver disease and control patients without liver disease were analyzed from the national inpatient sample. Incidence of VTE was compared in patients with mild, moderate‐severe or no liver disease, and the impact on in‐hospital mortality and length of stay was calculated. Results: The overall incidence of VTE for patients with no liver disease, mild liver disease and moderate‐severe liver disease was 2.7, 2.4 and 0.9 per 100 patient discharges, respectively. In the presence of VTE, in‐hospital mortality was 10.8%, 5.8%, and 21.7% for the no liver disease, mild disease and moderate‐severe liver disease, respectively. The presence of VTE resulted in an increase in mortality for patients with no liver disease (OR, 1.16; 95% CI, 1.14–1.18) and moderate‐severe liver disease (OR, 1.63; CI 95%, 1.42–1.88). Conclusions: Patients with moderate‐severe liver disease have a lower risk of VTE than those without liver disease. Development of thrombosis during admission increased the risk of in‐hospital mortality.